Interactive impact of zeolite with nitrogen sources on garlic yield under temperate agro-ecosystem of Azad Jammu and Kashmir - Bibi, Sadia; Khan, Muhammad Tariq; Hamid, Abdul; Jamil, Muhammad; Shafqat, Muhammad (Journal of Pure and Applied Agriculture, 2024)
Absorbable N (NO3–) leaching losses have been a challenge for a long time to agricultural scientists, in all types of vegetable and field crop production. Zeolites are alumino-silicate minerals that have the capacity to hold moisture, N and other nutrients due to large reactive surface area making sustainable N supply to plants throughout the cropping season. We studied the impact of various nitrogen sources like zeolite, poultry manure, and urea N individually and in combinations on garlic production. Zeolite, poultry manure, and urea along with combinations (3 only, 6 combinations and Control) comprising 10 treatments, were used to assess nitrogen supply during garlic crop and its yield under temperate agroecosystem. Combinations of zeolite, poultry manure, and urea positively enhanced biological yield, but differences among combinations were non-significant and significantly differed from the control and single source. Urea-nitrogen and poultry-manure combination at 60 + 60 kg ha-1 gave a maximum yield of garlic 8.7 tones ha-1; zeolite, Urea-Nitrogen and poultry-manure at 250 + 60 + 30 kg ha-1 yielded 7.68 tones ha-1. Poultry-manure plus zeolite, and poultry-manure plus urea combinations increased ascorbic acid 0.2 mg.100g-1 and antioxidant 0.2597 mg 100 g-1 in the garlic crop. Zeolite, urea, and poultry-manure at the doze of (500 kg + 30 kg + 30 kg ha-1) were proved to be the best dose, economical, and cost-effective. This study will help a common farmer to manage their crop fertilization in combinations for targeted biological and quality of yield contents by efficient nitrogen use through slow releasing and reduced leaching in temperate hilly areas with average to below average organic matter.